Mechanical Response and Structure Optimization of Nanomodified Asphalt Pavement - Wenjun Gu; Yao Tian; Xuanyu Zhang (Advances in Civil Engineering)
Nanomaterials are widely used in the preparation of modified asphalt because they can improve the high-temperature performance of matrix asphalt and have achieved good engineering results. However, the existing research mainly focuses on the material analysis and formula development of nanomodified asphalt and has not yet been involved in the mechanical response of the nanomodified asphalt pavement structure. The mechanical response contains the horizontal tensile stress and the vertical compressive stress of SiO2 modified asphalt pavement. It is unable to propose the matching pavement structure combination for the unique material characteristics of nanomodified asphalt, which leads to the increase of the possibility of pavement diseases and material waste. Hence, considering that semirigid base is the most widely used base type in China, two different structural models of nanomodified asphalt pavement are established according to the current specifications. The effects of pavement thickness, material type, and pavement design parameters on the mechanical response of nanomodified asphalt pavement are analyzed, and then the principle of optimal mechanical performance is taken and the optimal combination of nanomodified asphalt pavement structure is proposed.